2020
DOI: 10.1109/access.2020.2974974
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Method for Extraction of Complex Road Intersection Points From High-Resolution Remote Sensing Images Based on Fuzzy Inference

Abstract: Automatic extracting road intersection points is essential for applications such as data registration between vector data and remote sensing images, aircraft-assisted navigation. However, at a large scale, it is difficult to quickly and accurately extract road intersection points due to the problems caused by complex structures, geometric texture noise interference. In this context, taking OpenStreetMap (OSM) data as priori knowledge, we propose a method for automatic extraction of complex road intersection po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The suggested model's performance was assessed using the criteria of completeness (precision), correctness (recall), and quality (intersection over union [IoU]). These criteria were initially utilized in Wiedemann et al (39) and Wiedemann and Ebner (40) with the goal of extracting highway data, and they are now often used for performance evaluation of the related models (41,42). The following selection criteria are necessary for determining the performance evaluation metrics: The major goal of this case study is to assess the accuracy of the proposed model's predictions and contrast them with a GT data set.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested model's performance was assessed using the criteria of completeness (precision), correctness (recall), and quality (intersection over union [IoU]). These criteria were initially utilized in Wiedemann et al (39) and Wiedemann and Ebner (40) with the goal of extracting highway data, and they are now often used for performance evaluation of the related models (41,42). The following selection criteria are necessary for determining the performance evaluation metrics: The major goal of this case study is to assess the accuracy of the proposed model's predictions and contrast them with a GT data set.…”
Section: Resultsmentioning
confidence: 99%
“…location and shape) to support other downstream navigation tasks [15], [16]. It is regarded as the foundation of the route selection task [17], [18]. With the rise of AI for automated navigation, machine learning can now be used to digitise physical street features into map information.…”
Section: ) Environment Mappingmentioning
confidence: 99%
“… Types of intersection from Dai et al [ 83 ]: ( a – c ) typical road intersections; ( d – f ) complex intersections; ( g , h ) round-about intersection …”
Section: Figurementioning
confidence: 99%
“…Zhou and Li [82] identified nine types of intersections. Dai et al [83] classified junctions into three main classes: the typical road intersection structure (Figure 2a-c), the complex typical intersection structure (Figure 2d-f), and the round-about road intersection structure (Figure 2g,h), as shown in Figure 2. By analysing the various types of intersections, we found that there are 14 unique types of junctions.…”
Section: Intersection Detectionmentioning
confidence: 99%